Performance of concrete containing different ratios of metakaolin and magnetized water - Mostafa M. Keshta; Mohamed M. Yousry Elshikh; Ahmed M. Elkerany (Next Sustainability)
Metakaolin (MK) is an eco-friendly cementitious material. Incorporating MK as a partial or additive for cement in concrete can negatively affects its workability, especially at higher replacement levels, and may also adversely affect concrete strength. Magnetized water (MW) is a technique of treating regular tap (TW) water by exposing it to a magnetic field with a specific intensity and a certain number of cycles, making the water magnetized. The incorporation of MK and MW in concrete promotes sustainability by reducing cement consumption, thereby lowering carbon emissions. This research investigates the effects of using magnetized water (MW), prepared in a magnetic field of 1.4 tesla, on the workability and compressive strength of concrete containing MK in different ratios. MK was incorporated at 5 %, 10 %, and 20 % as either a partial replacement or additive to cement by weight. Two sets of concrete mixes were prepared: one with MK (ranging from 0 % to 20 % as a replacement and additive) mixed with ordinary tap water (TW), and the other with the same MK percentages mixed with MW. The results of the hardened concrete tests indicated that the optimal MK ratio for concrete was 10 + % (10 % as an addition to cement), whether or not MW was used. The slump of concrete decreased when TW was used; however, using MW improved the slump by up to 2 %. The compressive strength increased by 13 %, 11 %, and − 5 % at 7, 28, and 365 days, respectively, with no MK and the use of MW. When 10 + % MK was used with MW, the compressive strength improved by 5 %, 0 %, and − 5 % at 7, 28, and 365 days, respectively. Also, in the SEM images, the cement pastes in the presence of MK and MW became denser and more cohesive compared to the control mix without them, indicating an improvement in the hydration process with the efficient use of MW. Also, FTIR analysis was conducted to the optimal mixes to show the function groups of these mixes in microscale. Finally, the results of water properties indicated that using MW increase TDS and pH up to 14 % compared to using TW.